2020
DOI: 10.3329/ajmbr.v5i4.45269
|View full text |Cite
|
Sign up to set email alerts
|

Growth and economic performance of different supplementary feed on female mud crab (Scylla olivacea) fattening in plastic box

Abstract: The present study was conducted to identify low cost feed for female mud crab (Scylla olivacea) fattening practice in plastic box and the effect of different feeds on growth and survival rate of mud crab. A number of 30 adult non-gravid female crabs were reared into rectangular shaped plastic boxes, each box containing one crab. Three types of feed such as Chicken intestine, Tilapia and Apple Snail meat were supplied as feed at 10% of body weight of the crabs once daily considered as Treatment-1, Treatment-2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 11 publications
(12 reference statements)
2
9
0
Order By: Relevance
“…In the present study, T1 (fed with chicken intestine) recorded 100% survival, which was followed by T3 (90%), T2 (70%), and C (70%). Similarly, in another study Das et al (2020) obtained 100% survival with chicken intestine for orange mud crab Scylla olivacea. Mirera and Mtile (2009) obtained a lower survival rate of 45% with fish offal, whereas the current experiment recorded a higher survival rate of 70% with low-value fish.…”
Section: Survival Ratementioning
confidence: 72%
See 4 more Smart Citations
“…In the present study, T1 (fed with chicken intestine) recorded 100% survival, which was followed by T3 (90%), T2 (70%), and C (70%). Similarly, in another study Das et al (2020) obtained 100% survival with chicken intestine for orange mud crab Scylla olivacea. Mirera and Mtile (2009) obtained a lower survival rate of 45% with fish offal, whereas the current experiment recorded a higher survival rate of 70% with low-value fish.…”
Section: Survival Ratementioning
confidence: 72%
“…The major reason for the enhanced survival rate in the present study was that they were maintained in individual cages. This observation was supported by Das et al (2020), which have proven that crab culture in cages is found to be economically feasible, in contrast to open-pen culture because it ensures better survival and no cannibalism.…”
Section: Survival Ratementioning
confidence: 81%
See 3 more Smart Citations